Business Negotiations in ELF from a Cultural Linguistic Perspective - Mendes de Oliveira, Milene (Applications of cognitive linguistics ;, 2020)
Some of the most frequent questions surrounding business negotiations address not only the nature of such negotiations, but also how they should be conducted. The answers given by business people from different cultural backgrounds to these questions are likely to differ from the standard answers found in business manuals. In her book, Milene Mendes de Oliveira investigates how Brazilian and German business people conceptualize and act out business negotiations using English as a Lingua Franca. The frameworks of Cultural Linguistics, English as a Lingua Franca, World Englishes, and Business Discourse offer the theoretical and methodological grounding for the analysis of interviews with high-ranking Brazilian and German business people. Moreover, a side study on e-mail exchanges between Brazilian and German employees of a healthcare company serves as a test case for the results arising from the interviews, and helps understand other facets of authentic intercultural business communication. Offering new insights on English as a Lingua Franca in international business contexts, Business Negotiations in ELF from a Cultural Linguistic Perspective simultaneously provides a detailed cultural-conceptual account of business negotiations from the viewpoint of Brazilian and German business people and a secondary analysis of their pragmatic aspects.